2017
DOI: 10.1007/s10457-017-0152-z
|View full text |Cite
|
Sign up to set email alerts
|

The economic potential of fruit trees as shade in blue mountain coffee agroecosystems of the Yallahs River watershed, Jamaica W.I.

Abstract: Studies in coffee agroecosystems often focus on the conservation and environmental benefits of this managed novel habitat, but rarely examine the socioeconomic benefit of the shade tree products themselves to coffee farmers. An examination of Blue Mountain coffee farmers along an elevation gradient within the Yallahs River watershed saw several tree species emerge as important within the agroecosystems, accounting for approximately 10% of gross farm incomes. Of the 24 tropical, subtropical or temperate fruit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…These efforts have highlighted that traditional shade coffee systems provide viable habitat for taxa like birds, insects and mammals, including the early studies by Greenberg, which was the basis for the SMBC's creation of a shade certification for coffee-the Bird Friendly program (si.edu/ smbc). This research has also focused on the socio-economic benefits of coffee agroforestry systems-in particular the non-coffee products like fruits and wood that farmers can use or sell [71][72][73]. More recently, the ability of a shaded system to combat a number of the challenges that coffee farmers face due to climate disruption/change has also been discussed [72].…”
Section: Plos Onementioning
confidence: 99%
“…These efforts have highlighted that traditional shade coffee systems provide viable habitat for taxa like birds, insects and mammals, including the early studies by Greenberg, which was the basis for the SMBC's creation of a shade certification for coffee-the Bird Friendly program (si.edu/ smbc). This research has also focused on the socio-economic benefits of coffee agroforestry systems-in particular the non-coffee products like fruits and wood that farmers can use or sell [71][72][73]. More recently, the ability of a shaded system to combat a number of the challenges that coffee farmers face due to climate disruption/change has also been discussed [72].…”
Section: Plos Onementioning
confidence: 99%
“…Our work highlights the notion that farmers who increase the prevalence of nitrogen‐fixing leguminous trees will also support more habitat for insectivorous birds, which may increase benefits of pest control and maximize total crop yields by the farm. Although fruit trees provide additional crops to sell and thus resources for the community (Davis, Rice, Rockwood, Wood & Marra, ; Rice ), these short‐term benefits, while potentially beneficial during times of low coffee prices or destructive bouts of weather or disease, may not outweigh the loss of long‐term economic benefits of increased soil nitrogen and biological pest control provided by birds. Needed are studies that identify to what extent particular tree species, or combinations of tree species, influence pest control and subsequent coffee production, and at what scale such species must be used to supply meaningful gains for the farmer.…”
Section: Discussionmentioning
confidence: 99%
“…Just over half (51%) of the respondents indicated that they practice agroforestry. Agroforestry is widely promoted across Jamaica as an ecosystem-based adaptation practice with sound conservation value and economic potential for small farmers (Davis et al, 2017).…”
Section: Livelihood Satisfaction and Wild Food Harvestmentioning
confidence: 99%
“…In SIDS, biodiversity loss from traditional agroecosystems has been identified as one of the most serious threats to food and livelihoods security (Balzan et al, 2018). Agroecological approaches that included community planning, indigenous knowledge, attention to inequalities and a range of practices such as agroforestry, kitchen gardens, cover crops, polycultures, and forest conservation have been found to provide multiple co-benefits to food security, biodiversity conservation, improved well-being, and climate adaptation (Davis et al, 2017;Buckwell, 2019). Davis et al (2017) found that the food security challenges facing Jamaican farmers can be alleviated by improved marketing of fruit tree products-which also provide multiple benefits to watershed management.…”
Section: Livelihood Satisfaction and Wild Food Harvestmentioning
confidence: 99%